Differences in the chaperone-like activities of the four main small heat shock proteins of Drosophila melanogaster. - Morrow, G.; Heikkila, J.J.; Tanguay, R.M. (Cell Stress & Chaperones, 2006)
The Drosophila melanogaster family of small heat shock proteins (sHsps) is composed of 4 main members (Hsp22, Hsp23, Hsp26, and Hsp27) that display distinct intracellular localization and specific developmental patterns of expression in the absence of stress. In an attempt to determine their function, we have examined whether these 4 proteins have chaperone-like activity using various chaperone assays. Heat-induced aggregation of citrate synthase was decreased from 100 to 17 arbitrary units in the presence of Hsp22 and Hsp27 at a 1:1 molar ratio of sHsp to citrate synthase. A 5 M excess of Hsp23 and Hsp26 was required to obtain the same efficiency with either citrate synthase or luciferase as substrate. In an in vitro refolding assay with reticulocyte lysate, more than 50% of luciferase activity was recovered when heat denaturation was performed in the presence of Hsp22, 40% with Hsp27, and 30% with Hsp23 or Hsp26. These differences in luciferase reactivation efficiency seemed related to the ability of sHsps to bind their substrate at 42 degrees C, as revealed by sedimentation analysis of sHsp and luciferase on sucrose gradients. Therefore, the 4 main sHsps of Drosophila share the ability to prevent heat-induced protein aggregation and are able to maintain proteins in a refoldable state, although with different efficiencies. The functional reasons for their distinctive cell-specific pattern of expression could reflect the existence of defined substrates for each sHsp within the different intracellular compartments.